High stability of trehalose/maltose binding protein from Thermococcus litoralis makes it a good candidate as a sensitive element in biosensor systems for sugar control. Issue 3 (2010) - Povarova, Olga I.; Stepanenko, Olga V.; Sulatskaya, Anna I.; Kuznetsova, Irina M.; Turoverov, Konstantin K.; Staiano, Maria; Vitale, Annalisa; D'Auria, Sabato
Abstract : Fluorescence and circular dichroism in far-UV region were used to study the stability of trehalose/maltose binding protein (TMBP) from hyper thermophilic archaeon Thermococcus litoralis and its complex with glucose (TMBP/Glc). The evaluation of difference between free energy of native and unfolded state for TMBP and TMBP/Glc showed that both of them are several times higher than that of proteins from mesophilic organisms. Due to the high stability and innate ability to bind glucose this protein is a good candidate as a sensitive element in biosensor systems for sugar control.